Penyuluhan Dan Pelatihan Produksi Makanan Berbasis Tepung Rumput Laut Di Desa Tinangkung Kabupaten Bangkep - Sululing, Wadi; Mutalib, Yanti; Lutfie, Mukhtar (LPPM Universitas HKBP Nommensen, 2024)
This community-based empowerment (PBM) is entitled: Counseling and Training on Seaweed Flour- Based Food Production in Tinangkung Village, Bangkep Regency. This empowerment aims to empower the potential possessed by the seaweed cultivation group in Tinangkung Village, South Tinangkung District, Bangkep Regency. The problems faced by the